Heuristics of sustainable decision making: psychographic predictors of green purchase intention in the electric vehicle market - Jain, Priyal; Joshi, Meha (Journal of Social Review and Development, 2025)
Purpose: Transportation has now become one of the major contributors to greenhouse gas emissions, thereby exacerbating global warming. In response to this escalating peril of climate change, consumer behavior is undergoing a transformation aimed at environmental conservation. This evolution in consumer decision-making necessitates an examination of the green purchase intentions exhibited by consumers. The purpose of this research is to study various psychological factors that may influence the consumer’s intention towards electric vehicles. Methodology: This qualitative research study involves a comprehensive review of the existing literature to gather pertinent information. Findings: The study reveals that the theory of planned behavior and the technology acceptance model are central to this enquiry, which states that intention is the result of subjective norms, perceived behavioral control, attitude, perceived ease of use, and perceived usefulness. Originality: Only a few studies in the domain of sustainable consumer behavior have focused on the emerging industry of electric vehicles. Therefore, this study originally synthesizes the extant corpus of literature and highlights the role of psychological factors of consumer behavior towards electric vehicles. Limitation: This investigation is restricted to the exploration of psychological factors; however, various other dimensions, such as infrastructural, political, and product-related factors, may also significantly affect the purchase intention towards electric vehicles. Practical implication: Research findings will not only add to the existing corpus of literature but will furnish essential insights for policymakers and marketers in their initiatives to foster the adoption of electric vehicles.